Modification of 3 MSCT Parameters Using Iterative Reconstruction Techniques for Radiation Dose, Image Quality, and Anatomical Information - Simanungkalit, Nunut; Mardiyono, Mardiyono; Kartikasari, Yeti (International Journal Labs, 2023)
Cardiovascular Computed Tomography Angiography (CCTA) examination in diagnosing and evaluating congenital heart disease in pediatrics can make radiation exposure controversial and can lead to cancer risk. Development of parameter settings or modifications, namely tube voltage (kVp), pitch, and rotation time as an effort to optimize radiation dose to produce very low radiation dose. Apart from that, iterative reconstruction techniques are used as a reconstruction method to reduce noise to improve image quality. This study aimed to determine the effect of modifying 3 parameters using the iterative reconstruction technique on radiation dose, image quality, and anatomical information in pediatric CCTA examinations with clinical congenital heart disease at Harapan Kita Heart Hospital. Experimental research with a nonequivalent design. The results of this research are that the modification of 3 MSCT parameters and the iterative reconstruction technique produces a very low radiation dose which is significant at p = 0.000, with an average CTDIvol of 0.314 mGy, DLP 5.518 mGy.cm and can maintain different but not significant image quality, namely p = 0.72 in pulmonary artery SNR, p = 0.88 in ascending aorta SNR, p = 0.37 in pulmonary artery CNR and p = 0.41 in ascending aorta CNR so that it can provide anatomical information on contrast enhancement in the aorta and pulmonary artery area p = 0.02, extra cardiac analysis p = 0.04, contrast filling atria and ventricles p = 0.05, arterial and venous abnormalities p = 0.01, artifacts p = 0.17. Anatomical information is still informative in making a diagnosis. This study used a sample of 30 patients in the control group and intervention group using a purposive sampling method. Modification of 3 MSCT parameters with iterative reconstruction techniques provides an important contribution to the development of safe and informative scanning techniques for diagnosis.